The upregulation of hypoxia-related miRNA 210 in primary tumor of lymphogenic metastatic prostate cancer. (October 2018) - Eminaga, Okyaz; Fries, Jochen; Neiß, Susanne; Heitmann, Michaela; Wötzel, Fabian; Heidenreich, Axel; Bruns, Christiane; Alakus, Hakan; Warnecke-Eberz, Ute
Aim: To show the association between the expression level of hsa-miR-210 (miR-210) and tumor progression in prostate cancer (PCa).Methods: Quantitative PCR was performed to measure miR-210 on 55 subjects with different tumor stages; our results were then validated using three external datasets. ANOVA and Tukey's post hoc analysis were performed for comparative analyses between different tumor stages. Using the transcriptome data from The Cancer Genome Atlas for CaP, the gene expression analyses were performed on experimentally validated target genes of miR-210 identified in Tarbase and miRWalk datasets.Results & conclusion: miR-210 was significantly higher in N1 PCa compared with nonmetastatic PCa, whereas the metastatic tumor revealed a lower expression level of miR-210 than the primary tumor.